БЎЛАЖАК ТАСВИРИЙ САНЪАТ ЎҚИТУВЧИЛАРИНИНГ БАДИИЙ-КОНСТРУКТОРЛИК МАҲОРАТЛАРНИ ЎЗЛАШТИРИШИ - Нурметов, М.Р.; Сейитниязова, А.А.; Қалликлишов, Ш.О. (SCIENCE and SOCIETY, 2019)
In the article the attention is focused on the development of abilities and skills of art designing of students during out-of-class lessons.